Towards a Cultural Sociology of the Uses of Classical Literature: Deploying Literary Representations of Rome and the Romans in England between the 15th and 18th Centuries - Inglis, David; Thorpe, Christopher (Classical Literature, 2024)
Studies of receptions of ancient Greek and Roman literature analyze how so-called ‘classical’ texts are variously taken up and deployed by persons existing at later points in history. So far, the nature of such reception has not been conceptualized in an explicitly sociological manner. This paper proposes one way to do that, drawing upon key ideas developed by the Yale School of Cultural Sociology. This is done in order to re-narrate the ways in which ancient Roman texts were used by various interested parties in England, and later the United Kingdom, between the 15th and 18th centuries. The paper shows how Italian humanist understandings of the classicality of ancient Roman texts were taken up by English humanists, thereby purifying the overall set of such texts, rendering them seemingly context-free and adaptable to changing social circumstances. The relatively autonomous and free-floating nature of Roman literary texts defined as ‘classical’ allowed them to be taken up in different ways at different times for different purposes by different sorts of actors, especially aristocratic ones or those closely associated with aristocratic viewpoints. Texts describing republican Rome, and those depicting the transition from that political condition to the emergence of the Roman empire, were particularly appealing to English exegetes in the 17th and 18th centuries. They were deployed to make sense of the English Civil War and its aftermath, to carve out variant political identities, and to reflect upon the rise of the British Empire, which was understood to have surpassed its Roman counterpart, at the same time as it was feared that it might succumb eventually to a similar demise. The hopes and fears of English elites, as these were woven into the creation of political identities, were worked out through reflection upon and deployment of Roman texts taken to be timeless, processes that the paper models in a distinctive cultural sociological fashion.